EVALUATING THE EFFECTIVENESS OF OPTIMIZING PROGRAM OF DEVELOPMENT AND PSYCHOCORRECTION OF SOCIAL EXPECTATIONS OF PERSONALITY - Popovych, Igor (PSYCHOLOGICAL JOURNAL, 2017)
In the article, contensive and process features of optimizing program of correction and social expectations of personality are proved. It is defined principles and it is described organization and conditions of the forming phase of the study. It is posted training sessions and aftertraining support «Expective output». It is disclosed the essence of directions of forming and correctional phase of research program: forming and developing, prevention and correction. We can also outline appropriateness and content features of aftertraining support. A control stage of the pilot study has been realized. The main results of the implementation of program study of social expectations of personality are considered. It is evaluated the efficiency of the optimizing program of development and psychological correction of social expectations of personality. It is grounded a substantiation of received experimental research results. It is concluded that the implementation of the optimizing program of the development and psychological correction of social expectations provided the formation of ideas about effective realization of business processes, necessary skills of effective communication, management of the sale of goods. Application of combined model of educational training has allowed to consolidate above listed skills.